The Influence of Content Marketing Strategy and Promotion on Customer Loyalty at TOP Advertising: Pengaruh Strategi Konten Marketing dan Promosi terhadap Loyalitas Pelanggan di TOP Advertising - Deric Vesuvius; Petrus Loo (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the influence of Content Marketing Strategy and Promotion on Customer Loyalty at TOP Advertising. This study uses a quantitative method with primary data obtained through distributing questionnaires to 126 respondents using a saturated sample method. Data analysis was carried out using descriptive statistics, classical assumption tests, multiple linear regression, partial tests (t-tests), simultaneous tests (F-tests), and coefficient of determination (R²) tests. The results show that Marketing Strategy has a positive and significant effect on Customer Loyalty with a t-value of 1.660 > t-table 1.657 and a significance level of 0.000 < 0.05. This finding is in line with the research of Setiayasa et al. (2024) and Darado et al. (2023) which also stated that Marketing Strategy has a significant effect on Customer Loyalty. Meanwhile, Promotion does not have a significant effect on Customer Loyalty, with a t-value of 0.843 < t-table 1.657 even though it has a significance level of 0.000 < 0.05. Simultaneously, Marketing and Promotion Strategy does not have a significant effect on Customer Loyalty, indicated by the Fcount value of 1.770 < Ftable 3.07 with a significance of 0.000 < 0.05. The results of the determination coefficient (R²) test of 0.427 indicate that 42.7% of the variation in Customer Loyalty can be explained by Marketing and Promotion Strategy, while the remaining 57.3% is influenced by other factors outside this study, such as service quality, trust, and customer satisfaction.